BUILDING CUSTOMER LOYALTY ON CUSTOMER BANKING - Linda Sariningrum; Moch Zulfa (IJIBE (International Journal of Islamic Business Ethics), 2017)
The primary purpose of this research is to investigate and examine the effect of Shared Value Quality and Communication Quality on Customer Loyalty through Trust, and to propose an empirical model to investigate such relationships. A total of 100 customers of Syari’ah BNI Bank of Semarang completed questionnaires on Shared Value Quality, Communication Quality, Trust, and Customer Loyalty. Results from SmartPLS 3.0 based on structural equation modeling confirmed that Shared Value Quality and Communication Quality were positively related to Trust and Customer Loyalty; furthermore Trust was related to Customer Loyalty.Keywords : Shared Value Quality, Communication Quality, Trust,Customer Loyalty